H1:IC31 vaccination is safe and induces long-lived TNF-α+IL-2+CD4 T cell responses in M. tuberculosis infected and uninfected adolescents: A randomized trial. Issue 1 (3rd January 2017) - ,; Rozot, Virginie; Abrahams, Deborah A.; Mauff, Katya; Smit, Erica; Brown, Yolande; Hughes, E. Jane; Makgotlho, Edward; Keyser, Alana; Erasmus, Mzwandile; Makhethe, Lebohang; Africa, Hadn; et al.
Highlights: H1:IC31 vaccination was well tolerated and had an acceptable safety profile. Two vaccinations of 15 μg H1:IC31 induced the most durable immune response. H1:IC31 induced long-lived memory CD4 T cells that co-express TNFα and IL-2. Abstract: Background: Control of the tuberculosis epidemic requires a novel vaccine that is effective in preventing tuberculosis in adolescents, a key target population for vaccination against TB. Methods: Healthy adolescents, stratified by M. tuberculosis -infection status, were enrolled into this observer-blinded phase II clinical trial of the protein-subunit vaccine candidate, H1:IC31, comprising a fusion protein (H1) of Ag85B and ESAT-6, formulated with the IC31 adjuvant. Local and systemic adverse events and induced T cell responses were measured after one or two administrations of either 15 μg or 50 μg of the H1 protein. Results: Two hundred and forty participants were recruited and followed up for 224 days. No notable safety events were observed regardless of H1 dose or vaccination schedule. H1:IC31 vaccination induced antigen-specific CD4 T cells, co-expressing IFN-γ, TNF-α and/or IL-2. H1:IC31 vaccination of M.tb -uninfected individuals preferentially drove the emergence of Ag85B and ESAT-6 specific TNF-α + IL-2 + CD4 T cells, while H1:IC31 vaccination of M.tb -infected individuals resulted in the expansion of Ag85B-specific but not ESAT-6–specific TNF-α + IL-2 + CD4 T cells. Conclusions: H1:IC31 was safe and immunogenic in uninfected and M.tb -infected adolescents. Two administrations of the 15 μg H1:IC31 dose induced the greatest magnitude immune response, and was considered optimal (South African National Clinical Trials Register, DoH-27-0612-3947 ; Pan African Clinical Trial Registry, PACTR201403000464306 ).